PEDAGOGICAL KNOWLEDGE AND ITS REPRESENTATION IN SCIENTIFIC TEXT IN CONDITIONS OF “SEMIOLOGICAL TURN” (DIALOGUE WITH A.A. POLONNIKOV) - A. V. KORZHUEV; N. N. ANTONOVA (Высшее образование в России)
The article examines the contours of pedagogical semiology, reveals the criteria for the correspondence of scientific and pedagogical text to reader’s understanding adequate to author’s vision of phenomena described and the pedagogical reality. The paper is a response to the article of A.A. Polonnikov “Semiologic Turn” in Pedagogical Sciences published in Vysshee obrazovaniye v Rossii (2017, no. 10). The article presents a critical analysis of the issues of pedagogical semiotics and pedagogical texts. The authors cast doubt on the thesis of Polonnikov’s paper that “semiological turn” is caused by the gap between author as itself and textual person which indicates the change of discourse practice. The authors argue that researcher as a subject is inseparable from an object researched. This thesis may be intensified when applied to pedagogy. Pedagogical texts reflect personality’s features in three aspects: intellectual, emotional and volitional. The authors suggest instead of “semiological” searches to introduce a category “pedagogical text comprehended”.